PROCEDURAL STATUS OF CONFIDENTIAL WITNESS IN CRIMINAL PROCEEDINGS (ON THE EXAMPLE OF TURKISH CRIMINAL PROCEDURE LAW) - Sh.Kh.Mamatalieva (Scholar Express Journals, 2023)
In this thesis, the importance of the witness's participation in criminal proceedings, ensuring the safety of the witness, not disclosing the identity of the witness. In particular, the procedural status of a confidential witness, the procedure for their participation in the proceedings, is important and the need to be questioned as an anonymous person was analyzed on the basis of the Turkish Criminal Procedure Law
Keywords: : the procedural status of the witness; the witness; the procedural the procedural protection of the witness